A clinical study of ectopic pregnancy in a tertiary care hospital - Behera, Arati; Ghadei, Ranjita; Bal, Rudra Narayan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Ectopic pregnancy is a life-threatening emergency commonly encountered by medical practitioner. Diagnosis is frequently missed and should be considered in any women in the reproductive age group with abdominal pain or vaginal bleeding. The aim of the study is to assess the incidence, clinical presentation, risk factors, methods of diagnosis, treatment, outcome and complications. Methods: This was a prospective study at S.C.B. Medical college from January to December 2017. Parameters like age, parity, gestational period, risk factors, clinical presentations, findings on ultrasonogram and at surgery with morbidities associated with diagnosed cases of ectopic pregnancy (n=93) were noted and analysed with SPSS-19 software. Results: Incidence of ectopic pregnancy was 18/1000 deliveries. Maximum cases were in age group of 21 to 30 years (54.8 %) and parous (76.3%). Common risk factors were having history of abortions (46.2%), previous tubal sterilization (24.7%), having one or more caesarean section (17.2%) and h/o infertility (16.1%). Most common symptom was pain abdomen (96.8%). Commonest site was ampullo-isthmic region of tube and rupture was the commonest mode of presentation. All underwent laparotomy and unilateral salpingectomy was done in 86 % of cases. It contributed to 3.27 % of total maternal deaths. Conclusions: Suspicion in high risk group can direct one to investigate and diagnose early, thereby reducing morbidity, mortality and improving the prospect of future fertility.